1986
DOI: 10.1021/es00148a006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of atmospheric organic and elemental carbon particle concentrations in Los Angeles

Abstract: A fine particle air monitoring network was operated in the Los Anaeles area durin& 1982.It was found that carbonaceous aerosols accounted for typically 4~ of total fine particle mass loadings at most monitoring sites.The ratio of total carbon (TC) to elemental carbon (EC) in ambient samples and in primary source emissions was examined as an indica tor of the extent of secondary organic aerosol formation. It was found that TC to EC ratios at all sites on average are no higher than recent estimates of the TC to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
259
1
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(276 citation statements)
references
References 25 publications
13
259
1
3
Order By: Relevance
“…On the other hand, the composition of the fire aerosol itself suggests a reduced hygroscopicity, being $80% organic by mass, much higher than that typical for Los Angeles pollution [cf. Gray et al, 1986], though we have no chemical measurements on the 18th to confirm this for our specific case. Interestingly, our fire spectrum is consistent with recent measurements by Rissler et al [2004] on fire plume aerosols in Amazonia (shown in Figure 4), suggesting that such low hygroscopicity for fire aerosols may be common.…”
Section: Resultsmentioning
confidence: 80%
“…On the other hand, the composition of the fire aerosol itself suggests a reduced hygroscopicity, being $80% organic by mass, much higher than that typical for Los Angeles pollution [cf. Gray et al, 1986], though we have no chemical measurements on the 18th to confirm this for our specific case. Interestingly, our fire spectrum is consistent with recent measurements by Rissler et al [2004] on fire plume aerosols in Amazonia (shown in Figure 4), suggesting that such low hygroscopicity for fire aerosols may be common.…”
Section: Resultsmentioning
confidence: 80%
“…35,102,103 It accounts for OC not associated with any other sources and leads to results similar to those of Schauer and Cass. 101 A tracer solution CMB was tested by Gray et al 104 using EC as the marker for primary source types. 105 Assuming that primary OC and EC concentrations are correlated at a specific location because they have common sources, SOA is estimated as:…”
Section: Quantification Of Soamentioning
confidence: 99%
“…Understanding the composition of atmospheric aerosol particles is necessary for identifying their sources and predicting their effect on various atmospheric processes. Although organic compounds typically account for 10-70% of the total dry fine particle mass in the atmosphere (Gray et al, 1986;Middlebrook et al, 1998), organic PM concentrations, composition and formation mechanisms are not well understood, particularly in relation to the other major fine particle constituents, i.e. sulphate and nitrate compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These include the use of tracer compounds for either the primary or the secondary OC (Gray et al, 1986;Turpin and Huntzicker, 1991), the use of models describing the formation of secondary OC (Pandis et al, 1992) and the use of models describing the emission and dispersion of primary OC (Harley and Cass, 1995).…”
Section: Introductionmentioning
confidence: 99%